2016
DOI: 10.1063/1.4962169
|View full text |Cite
|
Sign up to set email alerts
|

Bovine serum albumin detection and quantitation based on capacitance measurements of liquid crystals

Abstract: Liquid crystal (LC)-based biosensing is generally limited by the lack of accurate quantitative strategies. This study exploits the unique electric capacitance properties of LCs to establish quantitative assay methods for bovine serum albumin (BSA) biomolecules. By measuring the voltage-dependent electric capacitance of LCs under an alternating-current field with increasing amplitude, positive correlations were derived between the BSA concentration and the electric capacitance parameters of LCs. This study demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 22 publications
1
22
0
3
Order By: Relevance
“…Although the data are somewhat scattered, the coefficient of determination r 2 for the linear fit is still greater than 0.92 in each case. When BSA was immobilized on a DMOAP-coated glass surface, we observed that the detection limit of BPLC-based protein assay, 10 −9 g/ml (15 pM) BSA, was similar to that based on voltage-dependent capacitance measurement of HDN, but was three orders of magnitude higher than that of the CLC-based protein assay (10 −12 g/ml), as described in our previous work [12,17]. Other studies on LC-based BSA detection demonstrated that biosensing with 5CB on a glass surface functionalized with gold nanoparticles resulted in a detection limit of 0.5 μg/ml (7.5 nM) BSA based on optical texture observation [26].…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…Although the data are somewhat scattered, the coefficient of determination r 2 for the linear fit is still greater than 0.92 in each case. When BSA was immobilized on a DMOAP-coated glass surface, we observed that the detection limit of BPLC-based protein assay, 10 −9 g/ml (15 pM) BSA, was similar to that based on voltage-dependent capacitance measurement of HDN, but was three orders of magnitude higher than that of the CLC-based protein assay (10 −12 g/ml), as described in our previous work [12,17]. Other studies on LC-based BSA detection demonstrated that biosensing with 5CB on a glass surface functionalized with gold nanoparticles resulted in a detection limit of 0.5 μg/ml (7.5 nM) BSA based on optical texture observation [26].…”
Section: Resultssupporting
confidence: 71%
“…By exploiting the Bragg reflection of CLC and transmission spectroscopy, the concentration of BSA can be correlated with the minimum transmittance or bandwidth of incident light [12]. Through the measurement of capacitance properties of LCs under an externally applied electric field, we observed that BSA quantitation can also be achieved by measuring the voltage-dependent capacitance of nematic LC cells containing immobilized BSA [17]. Nevertheless, quantitative biosensing technology based on LCs remains at an early stage of development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All these advantages lend LC-based biosensors great potential for the next generation of high-sensitivity, low-cost and label-free bioassays. Up to now, various investigations of LC-based biosensors have been reported [427][428][429][430][431][432]. Very recently, Lee et al reported a label-free protein (bovine serum albumin, BSA) quantitative detection by a dual-frequency LC (DFLC)-based biosensor [433].…”
Section: Biosensorsmentioning
confidence: 99%
“…However, some innovative applications of the capacitance, electrooptical, and dielectric measurements of LCs have emerged. The Lee group [58] reported a LC-based capacitive biosensor, whose LC cell can be considered a parallel-plate capacitor. LCs were homeotropically or vertically aligned by DMOAP firstly.…”
Section: Other Sensing Techniques Based On Lcmentioning
confidence: 99%